הנוסחה לגירוש שדים: "כך היא השבועה הזאת" - פורד, ג'יימס נתן (מחשבת ישראל, 2025)
This paper deals with the exorcistic formula “Thus Is This Oath.” The spell aims at expelling a standard list of assorted demons by putting them under oath in the name of God, referred to by the epithet gōʿēr wə-zōʿēf “the One who rebukes and censures,” and various angels, most notably Zaʿfiel. Zech 3:2 is then quoted as a precedent. The formula is attested in a considerable number of unpublished incantation bowls and in two partially published bowls, almost all written by the same practitioner. Although the basic formula is virtually identical in all the known parallels, the practitioner may add one or more of the following elements when composing the incantation: an introductory formula, a set of charaktêres, various verses from the Psalms, and/or a short closing formula or an independent spell-unit. This study presents editions of the two partially published magic bowls and five new parallels which illustrate the various ways the practitioner may compose his incantation. It concludes with a synoptic text of the basic spell in all twenty of the magic bowls with this formula catalogued by the author.